Households’ satisfaction with the healthcare services rendered by a ward-based outreach team in Tshwane district, Pretoria, South Africa - A. T. Masango Makgobela; J. V. Ndimande; G. Ogunbanjo; T. Bongongo; S. N. Nyalunga (South African Family Practice)
Introduction: Households’ satisfaction is an important and commonly used indicator for measuring quality in health care. An amelioration of primary health care services at the level of households, by utilising community health workers, has led to a good healthcare system in many countries, such as Brazil. In South Africa, little is known about the satisfaction of households (HH) regarding the healthcare services they receive from ward-based outreach teams (WBOTs). A study was undertaken to determine this phenomenon. Methods: The study used a cross-sectional study design. Tshwane district had established 39 ward-based outreach teams at the time of the study and households were conveniently selected. Hence the study population was estimated to be 3 600. Using 99% confidence level and 5% confidence interval, the sample size was 660, and oversampled to 765 since all households present during the data collection were willing to be included in the survey. Data collected was captured on Microsoft Excel and analysed using SAS, version 9.2. Results: Interviews were held with members of the families, who were willing to participate. Participants’ ages ranged from 18 to 110, mean age 53.1years (SD = 19.7). The study participants included more females (74.0%), and 45.2% were single. The majority (89.8%) were unemployed. Overall satisfaction was seen in 692 participants (90.7%). Outcome of satisfaction according to sex (91.9%), age (90.7%) and employment (90.8%) was not statistically significant with p-value 0.05. Conclusions: The findings of households’ satisfaction regarding the healthcare services rendered by the ward-based outreach team in Tshwane district, Pretoria, South Africa showed a high level of satisfaction from the households. This high level of satisfaction was referred to as excellent and was not associated with sex, age or employment status. A recommendation is made to all stakeholders that the ward-based outreach team programme cover all municipal wards in the country in order to raise the level of households’ satisfaction with the healthcare system.